The Effect of Cosheet Strategy-Based on Collaborative Creativity Learning on Energy Literation Ability and Physics Learning Outcome - Sri Astutik; Lu'luul Maknuniyah (Universitas Negeri Surabaya, 2022)
The purpose of this study was to find out how the energy literacy abilities of high school students while using Cosheet Strategy based on the Collaborative Creativity (CC) learning model and to determine the effect Cosheet Strategy based on the Collaborative Creativity (CC) learning model on physics learning outcomes in high school students. This type of research is experimental research with post-test only control group design. The study population was all students in Mumbulsari 1 Senior High School. The determination of the study sample used was cluster random sampling which was then obtained in class X Mathematics and Natural Science 3 as the experimental class and class X Mathematics and Natural Science 2 as the control class. The research instruments were observation, interviews, tests, and documentation. Analysis of research data for energy literacy skills is by using the energy literacy formula, while for physics learning outcomes use statistical tests on the SPSS application program. Based on the results of the analysis it can be said that students' energy literacy abilities while using the Cosheet Strategy based on Collaborative Creativity (CC) learning model are good, and the Cosheet Strategy based on Collaborative Creativity (CC) model has a significant effect on physics learning outcomes in high school students.